Gambaran Pengelolaan Obat di Instalasi Farmasi Rumah Sakit X Sangatta Tahun 2020 - Rena Handayani Alfian; Reksi Sundu; Nurul Fatimah (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Drug management at the Hospital Pharmacy Installation is very important to ensure the quality of drugs, in addition to maintaining the availability of pharmaceuticals to keep them in good condition, storage of pharmaceutical reparations is also important because to keep drugs from being damaged, not expired, avoiding dead stock and drug turnover. within 1 year running at maximum. This research is a descriptive non-experimental research. Qualitative data was obtained from observations using a check list form based on Permenkes number 72 of 2016. Quantitative data was based on tracking drug storage indicators, namely drug compatibility with stock cards, Turn Over Ratio (TOR), percentage of ED or damaged drug values. The results of the re-search at RS X Sangatta there were several storages that were not in accordance with predetermined standards. This can be seen from the results of the research conducted, the percentage is 33%, the results storage method is 80%, the storage component is obtained a percentage of 100%, 100% storage settings, 100% emergency medicine management, and 100% storage equipment. The results ofthe evaluation of drug stor-age at RS X Sangatta with drug storage indicators showed TOR results of 1.89 times/period, the percentage of expired or damaged drugs was 5.2%, the percentage of dead stock was 9.03% and the percentage of matched drugs with stock cards was 100%.